2015
DOI: 10.1017/s0376892915000041
|View full text |Cite
|
Sign up to set email alerts
|

Land ownership patterns associated with declining forest birds: targeting the right policy and management for the right birds

Abstract: SUMMARYFor over a century the foundation of biological conservation has been the development of open space networks either through outright public land acquisition or appropriate management of private lands. Because both approaches come with significant trade-offs, it is critical to understand which species are found across various land ownership types so that policy tools and management actions can efficiently be targeted to do the most good. In this paper, presence-only biological data were used to create sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Maslo et al. () found that the distribution of predicted habitat for our focal species is split evenly between publicly and privately owned forests.…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations
“…Maslo et al. () found that the distribution of predicted habitat for our focal species is split evenly between publicly and privately owned forests.…”
Section: Methodsmentioning
confidence: 92%
“…All the distribution models on which the maps are based provide a statistically reasonable depiction of the distribution of our focal species across our study area (AUC >0.70 [Maslo et al. ]). To provide a conservative estimate of where we believe each species is located the maps depicted only the top 10th percentile of probability of occurrence of all species in each of the 898,029 planning units.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Land ownership has implications for land management and can therefore have implications for biodiversity residing on it. For example, private versus publicly owned lands have different bird species compositions (Maslo, Lockwood and Leu 2015) and private temperate forests contain a greater diversity and density of microhabitats that can support greater biodiversity (Johann and Schaich 2016). Over one-quarter of the whole terrestrial land surface is managed or under the tenure rights of indigenous groups and this land intersects with approximately 40 per cent of protected areas and ecologically intact landscapes (Garnett et al 2018).…”
Section: Land Ownershipmentioning
confidence: 99%